NEUROLEPTICOS E O TRATAMENTO DO DELIRIUM NOS PACIENTES ONCOLÓGICOS EM CUIDADOS PALIATIVOS EXCLUSIVOS: HÁ DIFERENÇA NA EFICÁCIA ENTRE SUBCLASSES? - RIBEIRO, Felipe Silva (2020)
Introduction: Delirium is a neurological organic syndrome, usually acute and reversible, illustrated as an altered mental state that ranges from coma to agitation. It is highly prevalent in patients receiving palliative care, with higher rates later in life. The aim of this study is to compare the efficacy between haloperidol, olanzapine and risperidone in controlling delirium in cancer patients under palliative care. Method: The study was of an analytical, interventional nature, of the randomized, controlled, double blind, quantitative clinical trial type. Oncological patients in exclusive palliative care suspected of delirium were evaluated and those with confirmed diagnosis were subjected to drug treatment for a period of 7 days and evaluations every 24 h. Four groups were studied, one of which was a control group, where non-pharmacological measures were applied (NF GROUP), and three others who used the medications alone: risperidone (GR), olanzapine (GO) and haloperidol (GH). A sociodemographic and clinical questionnaire, a second questionnaire to assess delirium, the Confusion Assessment Method for Intensive Care Units "CAM - ICU", was used. In addition to the diagnostic scale, a symptom intensity scale was used to help measure the degree of patients' delirium, the CAM - ICU - 7. The treatment was considered effective when the patients completed the last 72 hours of the protocol without showing symptoms of delirium, using the doses recommended in the protocol, reaching a zero score on the intensity scale. This study was approved by the research ethics committee under opinion No. 2,683,075. Results: 291 patients with symptoms of delirium participated in the study, representing a prevalence of 86.5%, and the most common classification was hyperactive delirium (55.4%). The male gender was the most prevalent (53.4%), as well as the brown color (52.7%). About 80 patients (54.1%) had IPP over six and 75 (50.7%) had KPS of 40%. With regard to the use of psychotropic drugs, non neuroleptics, it was found that 134 participants (90.5%) had previously used the protocol under medical prescription. Among these, 119 patients (80.4%) used opioids and 110 (74.3%) exclusively used morphine (Table 1). Patients who have a history of seizures, dementia and depression have reduced efficacy in the treatment with the three drugs. Olanzapine and risperidone were able to reduce the symptom to zero on the fourth and sixth day of treatment, respectively. The average effective dose of risperidone was 3.52 mg and olanzapine 4.60 mg. Haloperidol, even reaching the dose of 5 mg (maximum dose of the protocol), was able to reduce the score on the severity scale by only 2 points. The non-pharmacological group did not reduce the symptom, maintaining the mean severity at the end of the protocol. Conclusion: When comparing the effectiveness between drugs, it can be seen that the drugs that obtained the best response were olanzapine and risperidone and that the treatment with haloperidol reduced, however, this reduction was not sufficiently satisfactory. Non-pharmacological treatment did not impact the severity scale.